2021
DOI: 10.3390/ijerph18052759
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial and Non-Financial Work Incentives on the Safety Behavior of Heavy Truck Drivers

Abstract: The goal of the research is to determine how compensation affects the safety behavior of truck drivers and consequently the frequency of traffic accidents. For this purpose, a survey was conducted on a sample of 220 truck drivers in international road transport in the EU, where the results of the Structural Equation Model (SEM) show that in the current state of the transport sector, financial and non-financial incentives have a positive impact on the work and safety behavior of drivers. Financial incentives al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The financial compensation in his research are career development, job design, training, work environment, participation and recognition. Meanwhile, Škerlič and Erčulj (2021) found that performance can be influenced by non-financial compensation. Skerlic and Vanja's research results also form the basis for corporate decision makers, because there is a very urgent and imperative need to re-identify sensors at the lowest employee level and recognize that non-financial sensors are very important and can improve performance acceptance systems in the transportation sector.…”
Section: Introductionmentioning
confidence: 99%
“…The financial compensation in his research are career development, job design, training, work environment, participation and recognition. Meanwhile, Škerlič and Erčulj (2021) found that performance can be influenced by non-financial compensation. Skerlic and Vanja's research results also form the basis for corporate decision makers, because there is a very urgent and imperative need to re-identify sensors at the lowest employee level and recognize that non-financial sensors are very important and can improve performance acceptance systems in the transportation sector.…”
Section: Introductionmentioning
confidence: 99%